Reverse crossed cerebellar diaschisis. - Ribeiro, Manuel (2006)
Cerebral Magnetic Resonance imaging in acute postictal period is performed to exclude structural processes that can be responsible for the epileptic activity. Sometimes, the findings are the result of the epileptic activity, and not the cause reflecting the pathophysiologic changes during epileptic activity. In this paper we describe a patient with status epilepticus who has developed hemicerebellar involvement contralateral to a frontal epileptogenic focus. This phenomenon of Reverse Crossed Cerebellar Diaschisis is rare and has been describe only in Single Photon Emission Computed Tomography (SPECT).